3D Printing Improved Testicular Prostheses: Using Lattice Infill Structure to Modify Mechanical Properties - Skewes, Jacob; Chen, Michael Y.; Forrestal, David; Rukin, Nicholas J.; Woodruff, Maria A. (Frontiers in Surgery, 2021)
Patients often opt for implantation of testicular prostheses following orchidectomy for cancer or torsion. Recipients of testicular prostheses report issues regarding firmness, shape, size, and position, aspects of which relate to current limitations of silicone materials used and manufacturing methods for soft prostheses. We aim to create a 3D printable testicular prosthesis which mimics the natural shape and stiffness of a human testicle using a lattice infill structure. Porous testicular prostheses were engineered with relative densities from 0.1 to 0.9 using a repeating cubic unit cell lattice inside an anatomically accurate testicle 3D model. These models were printed using a multi-jetting process with an elastomeric material and compared with current market prostheses using shore hardness tests. Additionally, standard sized porous specimens were printed for compression testing to verify and match the stiffness to human testicle elastic modulus (E-modulus) values from literature. The resulting 3D printed testicular prosthesis of relative density between 0.3 and 0.4 successfully achieved a reduction of its bulk compressive E-modulus from 360 KPa to a human testicle at 28 Kpa. Additionally, this is the first study to quantitatively show that current commercial testicular prostheses are too firm compared to native tissue. 3D printing allows us to create metamaterials that match the properties of human tissue to create customisable patient specific prostheses. This method expands the use cases for existing biomaterials by tuning their properties and could be applied to other implants mimicking native tissues.